IMPLEMENTASI PERATURAN MENTERI KEUANGAN NOMOR 190/PMK.07/2021 TENTANG PENGELOLAAN DANA DESA DI KECAMATAN BANG HAJI KABUPATEN BENGKULU TENGAH - Nopita, Reza; Wulandari, Wulandari; Suryaningsih, Patricia Ekowati (Jurnal Ilmiah Kutei, 2023)
Village Fund Direct Cash Assistance is assistance in the form of money given to poor families in villages originating from village funds to reduce the impact of the COVID-19 pandemic. In the process of distributing the Village Fund BLT, there are 6 criteria regulated in Article 33 paragraph (1) of the Minister of Finance Regulation Number 190/PMK.07/2021 concerning Village Fund Management. This study aims to find out how the implementation and inhibiting factors for implementing Minister of Finance Regulation Number 190/PMK.07/2021 concerning Management of Village Funds in Bang Haji District, Central Bengkulu Regency. This research is an empirical legal research. The results of this study indicate that the implementation of Minister of Finance Regulation Number 190/PMK.07/2021 concerning Management of Village Funds in Bang Haji District, Central Bengkulu Regency is not in accordance with Article 33 paragraph (1), where there should be several criteria for receiving Direct Cash Assistance (BLT). Village funds, but in Padang Burnai Village all residents receive BLT regardless of the criteria set by the central government, except for residents who have received other assistance from the government. Meanwhile, in Taba Tengah Village, BLT Village Funds were given to residents who met the criteria determined by the central government. As for the inhibiting factors in implementing the Minister of Finance Regulation Number 190/PMK.07/2021 concerning Management of Village Funds in Bang Haji District, they include the inhibiting factors from the Government side and from the Community side. Keywords: PMK No. 190, implementation, village funds, cash transfer.